Effective use of small-interfering RNA to characterize residual B-cell non-Hodgkin lymphoma cells following chemotherapy - Kusao, Ian K. T. (2012)
BACKGROUND: Children diagnosed with non-Hodgkin lymphoma (NHL) respond well to therapy resulting in relatively good prognosis. The exceptions are those who continue to have minimal residual disease (MRD). MRD NHL cells have been characterized as having increased mitochondrial DNA (mtDNA) copy numbers with increased expression of citrate synthase and isocitrate dehydrogenase. A proof-of-concept was designed to use small-interfering RNA (siRNA) as a tool to elucidate the relationship between citrate synthase and isocitrate dehydrogenase with cancer cell integrity. METHODS: mtDNA copy number and lactate dehydrogenase activities were assessed in chemotherapy-exposed residual NHL cells after introduction of siRNA against citrate synthase and/or isocitrate dehydrogenase expression. RESULTS: There was a significant decrease in lactate production in cells transfected with citrate synthase siRNA (p=0.02). Citrate synthase-silenced cells had decreased mtDNA copy numbers (p=0.03) compared to isocitrate dehydrogenase-silenced cells or combined citrate synthase- and isocitrate dehydrogenase-silenced cells. CONCLUSION: Inhibition of citrate synthase expression in siRNA-treated NHL cells resulted in decreased mtDNA copy numbers and lactate dehydrogenase expression. This observation needs further validation to determine the role of citrate synthase in mtDNA integrity and if citrate synthase siRNA could be a potential therapeutic modality in eradicating residual B-NHL cells.